The Sexual Trafficking of Women: Representations of Illegality and Victimisation - Santos, Boaventura de Sousa (2010)
Human trafficking in general and the trafficking of women in particular have been attracting increasing interest from states, international bodies, non-governmental organisations, the media and academia. The greater visibility conferred on this phenomenon has translated, on a national and international level, into policies designed to combat and prevent it, whose efficiency is debateable. This is the result not only of a lack of understanding of the specific features of the trafficking of women, but also of the fact that other objectives underlying the construction of these policies hardly meet the subjective needs and expectations of trafficked women. This article discusses some of the issues both emerging and absent from the legal framework for the sexual trafficking of women, with reference to the empirical situation of sexual trafficking in Portugal as analysed in the study Tráfico de mulheres em Portugal para fins de exploração sexual.